Public engagement in setting healthcare priorities: A ranking exercise in Cyprus - Farmakas, Antonis; Theodorou, Mamas; Galanis, Petros; Karayiannis, Georgios; Ghobrial, Stefanos; Polyzos, Nikos; Papastavrou, Evridiki; Agapidaki, Eirini; Souliotis, Kyriakos (My University, 2017)
In countries such as Cyprus the financial crisis and the recession have severely affected the funding and priority setting of the health care system. There is evidence highlighting the importance of population’ preferences in designing priorities for health care settings. Although public preferences have been thorough analysed in many countries, there is a research gap in terms of simultaneously investigating the relative importance and the weight of differing and competing criteria for determining healthcare priority settings. The main objective of the study was tο investigate public preferences for the relative utility and weight of differing and competing criteria for health care priority setting in Cyprus.
Keywords: Public participation; Healthcare priority setting; Resources allocation; Health policy